Actin protrusions push at apical junctions to maintain E-cadherin adhesion - Li, John Xiao He (Proc Natl Acad Sci U S A, 2020)
Cadherin-mediated cell–cell adhesion is actin-dependent, but the precise role of actin in maintaining cell–cell adhesion is not fully understood. Actin polymerization-dependent protrusive activity is required to push distally separated cells close enough to initiate contact. Whether protrusive activity is required to maintain adhesion in confluent sheets of epithelial cells is not known. By electron microscopy as well as live cell imaging, we have identified a population of protruding actin microspikes that operate continuously near apical junctions of polarized Madin-Darby canine kidney (MDCK) cells. Live imaging shows that microspikes containing E-cadherin extend into gaps between E-cadherin clusters on neighboring cells, while reformation of cadherin clusters across the cell–cell boundary correlates with microspike withdrawal. We identify Arp2/3, EVL, and CRMP-1 as 3 actin assembly factors necessary for microspike formation. Depleting these factors from cells using RNA interference (RNAi) results in myosin II-dependent unzipping of cadherin adhesive bonds. Therefore, actin polymerization-dependent protrusive activity operates continuously at cadherin cell–cell junctions to keep them shut and to prevent myosin II-dependent contractility from tearing cadherin adhesive contacts apart.